Complementarities between innovation policies in emerging economies. The case of Argentina's software sector - Motta, Jorge Jose (2013)
This paper analyses the presence of complementarity and substitutability relations between innovation policies in the software sector from Argentina. Supermodularity and submodularity tests between obstacles to innovation were performed with technological data from 257 Argentinean software firms, for the period 2008 to 2010. This research adds empirical evidence on the complementarities and supplementarities of innovation policies in an emerging economy and in a knowledge intensive business services sector. This kind of analysis allows to evaluate the convenience to attack jointly or separately a set of obstacles or separately. The results show multiple feedback relations between diverse obstacles and consequently between policies, and the main finding is that, in this emerging economy, innovation policies aimed to encourage firms to become innovators serve as well as an incentive for innovative firms to increase and intensify its innovation performance.